Synthetic biology tools for metabolic engineering - Ma, Hongwu (Henry Stewart Talks, 2026)
Metabolic engineering, Methods/ tools for genome scale metabolic network (GEM) reconstruction, MEMOTE: tool for metabolic model test, BiGG model database, Flux balance analysis, COBRApy and CAVE demos